Detection of mild cognitive impairment in an at-risk group of older adults: can a novel self-administered serious game-based screening test improve diagnostic accuracy? - Zygouris, Stelios; Iliadou, Paraskevi; Lazarou, Eftychia; Giakoumis, Dimitrios; Votis, Konstantinos; Alexiadis, Anastasios; Triantafyllidis, Andreas; Segkouli, Sofia; Tzovaras, Dimitrios; Tsiatsos, Thrasyvoulos; Papagianopoulos, Sotirios; Tsolaki, Magda (Journal of Alzheimer's disease, 2020)
Background: Literature supports the use of serious games and virtual environments to assess cognitive functions and detect cognitive decline. This promising assessment method, however, has not yet been translated into self-administered screening inst